An evaluation of the 25 by 25 goal for premature cardiovascular disease mortality in Taiwan: an age-period-cohort analysis, population attributable fraction and national population-based study. Issue 2 (7th August 2017) - Su, Shih-Yung; Lee, Wen-Chung; Chen, Tzu-Ting; Wang, Hao-Chien; Su, Ta-Chen; Jeng, Jiann-Shing; Tu, Yu-Kang; Liao, Shu-Fen; Lu, Tzu-Pin; Chien, Kuo-Liong
Abstract : Objectives: The aim of the 25 by 25 goal is to reduce mortality from premature non-communicable diseases by 25% before 2025. Studies have evaluated the 25 by 25 goal in many countries, but not in Taiwan. The aim of this study was to estimate the 25 by 25 goal for premature mortality from cardiovascular diseases in Taiwan. Methods: We applied the age-period-cohort model to project the incidence of premature death from cardiovascular disease from 2015 to 2024 and used the population attributable fraction to estimate the contributions of targeted risk factors. The probability of death was used to estimate the percent change. Results: The percent change in business-as-usual trend during 2010-2024 was only a 6% (range 1.7-10.7%) lower risk of premature mortality from cardiovascular disease among men. The greatest reduction in the risk of mortality occurred with a 30% reduction in the prevalence of smoking; however, there was only a 14.5% (10.6-18.3%) decrease in percent change and in the corresponding number of men (3706: range 3543-3868) who were prevented from dying. More than a 25% reduction in the percent change of premature cardiovascular disease mortality among women was achieved without control of any risk factor. To reach a 25% reduction in men before 2025, there needs to be a 70% reduction in the prevalence of smoking to reduce mortality by 26.2% (22.9-29.3%). Conclusions: Cigarette smoking is the primary target in the prevention of cardiovascular disease. Through the stringent control of smoking, the goal of a 25% reduction in premature mortality from cardiovascular disease may be achieved before 2025 in Taiwan.